STUDI KASUS LONDON SEBAGAI KOTA GLOBAL - Wijaya, Karen (Universitas Tarumanagara, 2024)
In this era of globalization, there are several large cities that have become centers of global economic and cultural activities. Several large, influential cities have become centers of global class activities and are even classified as Alpha cities, such as the city of London. The existence of the city of London is taken as a case study in this article because the City of London has been recognized as a city with an important presence in the global or world economic system, or as a Global Financial Center. The primary aim of this Paper is to outline results and to summarize research findings on the global city of London as a case study amidst all the dynamics of conditions currently occurring. This paper focuses on discussing strategies, the process of developing the global city of London as the world's financial center in anticipating possible risks and looking at development scenarios under the influence of a pandemic, and the development of digital technology. The research method used is a literature study approach related to articles with a discussion of themes containing keywords according to the research theme. The research conclusion obtained is that the city of London needs to maintain the quality status of its city performance and continue to stimulate economic conditions. Dynamics of change can occur due to many factors and cannot always be predicted. The presence of creative economy clusters and startups that are able to commercialize unique ideas has a big influence on the city's prosperity and provides economic growth even in times of uncertainty. Digital access can also create opportunities and expand access to vital support. Adapting to changes in behavior to digital also still requires socialization that is not instant. The City of London is still trying and continues to struggle endlessly to continue to be more advanced and better in various conditions. Keywords: global city, city of London, sustainable city, resilient city, creative city, and smart city Abstrak Pada era globalisasi ini terdapat beberapa kota besar yang menjadi pusat kegiatan ekonomi dan budaya secara global. Beberapa kota besar yang berpengaruh tersebut menjadi pusat kegiatan kelas global dan bahkan diklasifikasikan ke dalam kota Alpha, seperti kota London. Keberadaan kota London diambil sebagai studi kasus pada tulisan ini karena kota London sudah diakui sebagai kota yang keberadaannya penting di dalam sistem ekonomi global atau dunia, atau sebagai Global Financial Center. Tujuan utama dari makalah ini adalah untuk menguraikan hasil dan meringkas temuan penelitian tentang studi kasus kota global London di tengah seluruh dinamika kondisi yang terjadi saat ini. Makalah ini berfokus pada pembahasan strategi, proses pengembangan kota global London sebagai pusat finansial dunia dalam mengantisipasi resiko yang mungkin dan melihat skenario pengembangan di dalam pengaruh pandemi dan perkembangan teknologi digital. Metode penelitian yang digunakan adalah pendekatan studi pustaka terkait artikel-artikel dengan pembahasan mengenai tema yang berisi kata kunci sesuai tema penelitian. Kesimpulan penelitian yang didapatkan adalah kota London perlu mempertahankan status kualitas performa kotanya dan tetap menggiatkan kondisi ekonomi. Dinamika perubahan dapat terjadi karena banyak faktor dan tidak selalu dapat diprediksi. Hadirnya cluster ekonomi kreatif dan startup yang mampu mengkomersilkan ide yang unik memberikan pengaruh yang besar pada kemakmuran kota dan memberikan pertumbuhan ekonomi bahkan disaat ketidakpastian. Akses digital pun mampu menciptakan peluang dan memperluas akses ke dukungan vital. Adaptasi perubahan perilaku menjadi digital juga masih memerlukan sosialisasi yang tidak instan. Kota London masih berusaha dan terus berjuang tanpa henti untuk terus lebih maju dan lebih baik dalam berbagai macam kondisi.